The Effectiveness of Text Completion Technique towards Students’ Speaking Skill - Nursabrina, Nursabrina (Journal of English Education Studies, 2018)
This research paper aims to investigate the Effectiveness of text Completion Technique towards Students’ Speaking Skill at Eleventh Grade of Madrasah Aliyah Mathla’ul Anwar Pusat Menes. The research paper employs the quantitative research, with the quasy experimental design. Then, the researcher uses observation and performance test in which students of both classes use procedural text as the specific speaking material. In the data collecting technique, it compares pre-test and post-test results of both experimental and control class. Therefore, to analyze the data, the researcher used statistical computation. It works to count scoring, the result of the test, calculating the mean of both experimental and control class. Besides that, it calculated the standard deviation of each group and then found out the significant difference by using t-test. Based on the result of data analysis and interpretation of the research, it is clear that there is a significant difference after teaching speaking by using text completion technique in experimental class and teaching speaking by using lecture technique in control class.